2019
DOI: 10.1177/1179556519862280
|View full text |Cite
|
Sign up to set email alerts
|

Does Ramadan Fasting Affect Spirometric Data of Healthy Adolescents?

Abstract: Purpose: Several studies raised the effects of Ramadan fasting on healthy adults spirometric data, but none was performed in children. The aim of this study was to compare the spirometric data of a group of faster adolescents (n = 26) with an age-matched non-faster one (n = 10). Methods: This comparative quasi-experimental study, including 36 healthy males aged 12 to 15 years, was conducted during the summer 2015 (Ramadan: June 18 to July 16). Three sessions (Before-Ramadan [Before-R], Mid-Ramadan [Mid-R], Aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 35 publications
2
6
0
Order By: Relevance
“…The aforementioned finding is not sustained by this study since the two groups of fasters and non-fasters included similar percentages of boys with a “clinically significant” 6MWD decrease (57.69% vs. 30.00%, respectively). The present study result is not surprising since the respiratory system adapts normally during RO (Ben Fraj et al, 2019). A recent study concluded that “RO had no interaction effect with the spirometric data of healthy boys” (Ben Fraj et al, 2019).…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…The aforementioned finding is not sustained by this study since the two groups of fasters and non-fasters included similar percentages of boys with a “clinically significant” 6MWD decrease (57.69% vs. 30.00%, respectively). The present study result is not surprising since the respiratory system adapts normally during RO (Ben Fraj et al, 2019). A recent study concluded that “RO had no interaction effect with the spirometric data of healthy boys” (Ben Fraj et al, 2019).…”
Section: Discussionsupporting
confidence: 73%
“…The present study result is not surprising since the respiratory system adapts normally during RO (Ben Fraj et al, 2019). A recent study concluded that “RO had no interaction effect with the spirometric data of healthy boys” (Ben Fraj et al, 2019). For example, during the Pre-R, Mid-R, and Post-R ECs, there was no significant difference between the fasters and non-fasters groups’ mean forced expiratory volume in 1 s (101 ± 13 vs. 96 ± 16; 98 ± 11 vs. 97 ± 16; 101 ± 10 vs. 98 ± 16%, respectively; Ben Fraj et al, 2019).…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…It has been reported that a 30-day IF, such as RF, showed a significant increase in the levels of some gene products that correlated with immune system regulation, neuropsychiatric disorders, DNA repair and carcinogenesis, that is, RF developed a serum proteome protecting against cancer, obesity, metabolic syndrome, inflammation, as well as numerous neuropsychiatric disorders [111]. Also, Ben Fraj et al [112] have concluded that RF has no impact on the lung function, and this was evaluated by using spirometry test and comparing spirometric data between the fasting and nonfasting healthy adolescents aged 12-15 years. The same observation has been reported among adults [113].…”
Section: Rf and Medical Conditionsmentioning
confidence: 99%